Pengaruh Penerapan Green Accounting Terhadap Profitabilitas pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2019-2021 - Nadilla Rahayu; Abdul Wahid Mahsuni; Arista Fauzi Kartika Sari (Universitas Islam Malang, 2023)
The survival of a company depends on the company's ability to meet economic and social goals. Good company performance followed by good environmental performance can also increase good competitiveness for the company in the eyes of its stakeholders. Further developing the organization's ecological execution requires the idea of natural maintainability, one of which is the idea of green bookkeeping or otherwise called the idea of ecological bookkeeping. The concept of green accounting contains how companies disclose their environmental costs presented in financial reports to align company development with environmental functions and the distribution of benefits to the community around the company. The purpose of this study was to determine the effect of implementing green accounting on profitability in manufacturing companies listed on the IDX in 2019-2021. Sampling obtained 40 companies with 3 years of research so that the total becomes 120 samples based on the criteria applied. This study uses a multiple linear regression model. The results of this study indicate that environmental performance, environmental disclosure and environmental costs simultaneously have a significant effect on profitability. environmental performance has a significant negative effect on profitability. environmental disclosure has no significant effect on profitability. environmental costs have a significant negative effect on profitability.Keywords: Environmental performance, environmental disclosure, environmental costs, profitability.